Driving climate change : cutting carbon from transportation - Sperling, Daniel; Cannon, James Spencer, 1949- (Elsevier, 2007)
Climate change is one of the greatest challenges facing global society. The debate over what to do is confounded by the uncertain relationship between increasing greenhouse gas emissions and climate change, and the impact of those changes on nature and human civilization. This book will provide professionals and students alike with the latest information regarding greenhouse emissions while presenting the most up-to-date techniques for reducing these emissions. It will investigate three broad strategies for reducing greenhouse gas emissions: 1) reducing motorized travel, 2) shifting to less energy intensive modes, and 3) changing fuel and propulsion technologies. Findings will be presented by the leaders in the field with contributions from professors, researchers, consultants and engineers at the most prominent institutions - commercial, academic and federal - dealing with environmental research and policy. * Includes a comprehensive evaluation of current industrial practice * Provides technologically sound and manageable techniques for engineers, scientists and designers * Incorporates guidelines for a sustainable future.